2020
DOI: 10.1101/2020.06.03.131219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovering compounds mimicking calorie restriction using mammalian gene expression profiles

Abstract: Obesity is a risk factor for cardiovascular diseases, diabetes and cancer. In theory the obesity problem could be solve by the adherence to a calorie restricted diet, but that is not generally achieved in practice. An alternative is a pharmacological approach, using compounds that trigger the same metabolic changes associated with calorie restriction. Here I expand in the pharmacological direction by identifying compounds that induce liver gene signature profiles that mimic those induced by calorie restriction… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…I have previously introduced a gene expression analysis to identify candidate compounds inducing a specified gene signature in a specified tissue 8 . For sake of selfconsistency, I transcribe sections of that methodology here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I have previously introduced a gene expression analysis to identify candidate compounds inducing a specified gene signature in a specified tissue 8 . For sake of selfconsistency, I transcribe sections of that methodology here.…”
Section: Methodsmentioning
confidence: 99%
“…To identify compounds that induce the serine synthesis from 3-phosphoglycerate I took advantage of a toxicology study reporting the gene expression profiles of rats exposed to different compounds, including several drugs currently in use to treat a variety of illnesses 16 . I have previously shown that this resource can be used to identify compounds that mimic calorie restriction 8 . Here I will use the same approach to identify compounds that induces serine synthesis.…”
Section: Pharmacological Interventions Livermentioning
confidence: 99%